ENGAGING TO NURTURING: ENGLISH LANGUAGE TEACHING STRATEGIES AND CONSTRAINTS FOR VERY YOUNG MUSLIM LEARNERS AT KINDERGARTEN IN ACEH - Saiful Akmal; Yuliar Masna; Lianita Ali Nasution (Islam Futura, 2021)
The use of English language for very young learners in kindergarten has become fundamental in recent global teaching development, including in Aceh, Indonesia. Therefore, this qualitative research is aimed to discover the English language teaching strategies applied for very young Muslim learners’ at Kiddos English School (KES) Kindergarten, Banda Aceh. The research participants were selected by using non-probability sampling method. Furthermore, semi-structured interview towards four English teachers and participant observation was conducted in two classes of KES. The result of this study showed that KES teachers implemented at least seven strategies to teach English for their students from engaging learners in daily oral language activity, to establishing a nurturing environment, playing games, storytelling, audio-visual, singing, and teaching face to face. Furthermore, the teachers faced four constraints in applying those strategies, which are: students’ misbehavior, inconsistency of students’ attendance, lack of parental involvement, and insufficient number of teacher.